2008
DOI: 10.1021/jo8001112
|View full text |Cite
|
Sign up to set email alerts
|

Stilbene Oligomers from Parthenocissus laetevirens: Isolation, Biomimetic Synthesis, Absolute Configuration, and Implication of Antioxidative Defense System in the Plant

Abstract: Five new stilbene oligomers, laetevirenol A-E (4-8), were isolated from Parthenocissus laetevirens, together with three known stilbene oligomers (2, 3, and 9). The structures of the new compounds were elucidated by spectroscopic analysis, including 1D and 2D NMR experiments. Afterward the absolute configurations were determined. Biomimetic transformations revealed a possible biogenetic route, where stilbene trimers were enzymatically synthesized for the first time. In addition, their antioxidant activities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 40 publications
2
77
0
Order By: Relevance
“…-Compound 1 was isolated as a colorless amorphous powder, and its molecular formula was established as C 56 H 42 O 12 , on the basis of NMR and HR-ESI-MS data, which suggested that 1 was a resveratrol tetramer (resveratrol (Table, signals of C(1a) to those of HÀC(14c)), which has been previously isolated from P. quinquefolia [14] and P. laetevirens [17], revealed that 1 contained parthenocissin B as partial structure (resveratrol units A, B, and C). Compound 1 showed signals (Table, signals of C(1d) to those of HÀC(14d)) corresponding to an additional resveratrol unit D, which was confirmed by HMBC data (Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…-Compound 1 was isolated as a colorless amorphous powder, and its molecular formula was established as C 56 H 42 O 12 , on the basis of NMR and HR-ESI-MS data, which suggested that 1 was a resveratrol tetramer (resveratrol (Table, signals of C(1a) to those of HÀC(14c)), which has been previously isolated from P. quinquefolia [14] and P. laetevirens [17], revealed that 1 contained parthenocissin B as partial structure (resveratrol units A, B, and C). Compound 1 showed signals (Table, signals of C(1d) to those of HÀC(14d)) corresponding to an additional resveratrol unit D, which was confirmed by HMBC data (Fig.…”
mentioning
confidence: 98%
“…is usually planted as a cover crop in east China and traditionally used as folk medicine for the treatment of rheumatism, furuncle, and chronic ulcer [16]. Recently, we have reported the isolation of five new resveratrol oligomers together with three known ones from P. laetevirens [17]. Shortly after, further phytochemical studies led to the first occurrence of stilbene tetramers in this genus with a novel skeleton.…”
mentioning
confidence: 99%
“…These compounds inhibit fungal growth by interfering with microtubule assembly (Woods et al, 1995), disrupting plasma membranes, and uncoupling electron transport in fungal spores and germ tubes (Pezet and Pont, 1990). Stilbenes have also been shown to protect plants against oxidative stress (Rosemann et al, 1991;Adrian et al, 1996;He et al, 2008), to deter herbivores (Torres et al, 2003), and to inhibit the growth of competing plants (Fiorentino et al, 2008). However, their functions in conifers are poorly studied despite their abundance in widespread genera, such as spruce and pine.…”
mentioning
confidence: 99%
“…Free radical scavenging activity was evaluated with DPPH assay, as described previously (Luo et al, 2002;He et al, 2008). The reaction mixtures containing 180 μl of 150 μmol/L DPPH in ethanol and 20 μl of sample solutions (2-fold serial dilutions) were added to a 96-well microplate and then maintained at 37 °C until the reaction plateau was reached (30 min).…”
Section: Dpph Free Radical Scavenging Assaymentioning
confidence: 99%